Continuous intraocular pressure variations following positional transitions in normal subjects and open angle glaucoma patients using a contact lens sensor system - Zhang, Yuning; Yang, Wenxin; Chen, Zidong; Zhang, Xinyi; OR, Ping Wai; Lee, Ching Hymn Christopher; Karunaratne, Isuru Kaweendra; Xu, Yunzhi; Liu, Pingping; Chong, Iok Tong; Qin, Zhen; Lam, David C. C.; et al. (Graefe's archive for clinical and experimental ophthalmology, 2025)
Purpose To evaluate the efficacy of a novel contact lens sensor system (CLS) in detecting continuous intraocular pressure (IOP) variations following positional transitions, and to explore these IOP variation patterns among normal subjects, untreated glaucoma patients, and untreated ocular hypertension (OHT) subjects. Methods This prospective comparative study included 20 normal subjects, 14 high tension glaucoma (HTG) patients, 16 normal tension glaucoma (NTG) patients, and 14 OHT subjects. Participants wore the CLS for continuous IOP monitoring while undergoing sequential body position changes: from sitting to supine to a 10° head-down tilt (HDT), with each position maintained for ten minutes. Continuous IOP parameters, including mean, peak, and fluctuation (peak minus valley) in each position, as well as increment (peak minus starting value), interval (time to arrive peak), and velocity (increment divided by interval) after two position transitions, were compared among different positions and groups, respectively. Results Normal subjects, HTG and NTG patients exhibited higher CLS IOP mean and peak in supine/HDT positions compared to sitting ( P < 0.05), but the mean or peak in HDT did not significantly differ from that in supine ( P > 0.2). In OHT, all IOP parameters showed no significant difference among various positions ( P > 0.1), except for velocity. Comparisons among groups revealed that during the transition from sitting to supine, HTG demonstrated higher IOP increment than other three groups and higher velocity than normal subjects ( P < 0.05). NTG patients exhibited no significant differences in IOP increment, interval and velocity, compared to normal subjects ( P > 0.05). Conclusions The CLS proved effective in continuously recording IOP responses following positional changes in normal and glaucomatous eyes. Transitioning from sitting to supine resulted in increased IOP among normal subjects, HTG and NTG patients, but not in OHT. Compared to normal subjects, this IOP increase was more pronounced and rapid in HTG, but comparable in NTG. Key messages What is known Positional transitions can induce IOP variations, which differ among normal subjects and glaucoma patients, and potentially relate to glaucomatous neuropathy. However, prior findings are constrained by the discontinuity of traditional tonometry. What is new This study utilized a novel contact lens sensor system (CLS) to continuously monitor IOP during positional transitions in normal subjects and untreated glaucoma/OHT subjects. Continuous IOP outcomes revealed that normal subjects, HTG patients, and NTG patients exhibited an increase in IOP when transitioning from sitting to supine, whereas OHT did not. Compared to normal subjects, this increase in IOP was more pronounced and rapid in HTG patients, but similar in NTG.